Comparison of backpropagation and ERNN methods in predicting corn production. (2022) - Putro, Sigit Susanto; Syakur, Muhammad Ali; Rochman, Eka Mala Sari; -, Husni; -, Musfirotummamlu'ah; Rachmad, Aeri
No abstract available